Identifying priority locations to protect a wide-ranging endangered species. (January 2023) - Peters, Natasha M.; Kendall, Corinne J.; Davies, Jacob G.; Bracebridge, Claire; Nicholas, Aaron; Mgumba, Msafiri P.; Beale, Colin M.
Abstract: 1. Medium and large scavengers often move long distances to locate sufficient foraging areas, often including buffer zones of protected areas, putting them at considerable risk from geographically dispersed threats. 2. Vultures are declining worldwide with poisoning being the greatest threat in Africa. Using a novel capture-recapture model applied to carcasses found by 51 GPS tracked vultures, we estimated the exposure, threat, and risk of poisoning to vultures in southern Tanzania. Exposure to poisoning was defined as the areas that vultures use and where carcasses are likely to be found by a given individual. We used a human footprint map as a proxy for threat, identifying locations where poisoning was possible. Risk of poisoning was determined as areas with an overlap of exposure and threat. 3. We found that locations with the greatest risk of poisoning were within 20 km of protected areas. Although most high-risk areas we identified fell within this buffer, our risk assessment method identified additional hot-spots including some high-risk areas that fell outside nearby buffers. 4. We found that our risk assessment allowed us to identify more localised, high-risk areas that cover a much smaller total area. This gives more precise insight into where conservation management should be prioritised and limited resources should be focused.